Channeling John Dewey: What Would Vermont's Philosopher of Democracy Have to Say About Personalized Learning? - Kathleen R Kesson Dr. (Middle Grades Review, 2021)
In John Dewey’s educational framework, the process and product are inseparable; achieving democratic ends cannot result from undemocratic means. For him, the full humanization of people depended not upon externally imposed curriculum and management systems, but rather on responding to the intrinsic needs, interests, and powers of the individual to be educated. The trend in many states on personalized learning, flexible pathways, and proficiency-based assessment, provides a foundation for transforming the conventional system of education, with its standardization, testing, and grading towards Dewey’s vision of a more socially just, inclusive, and (small d) democratic system. So, what might Dewey have to say about personalized learning as a model with the potential to revolutionize the entrenched system? This essay addresses five problem-situations and questions that might merit his consideration: The contradiction between personalization and the creation of democratic community-building; Corporate interest in personalized learning, and the ‘perils of the personalized playlist’; Shifting from individual to ecological intelligence; Challenging the ‘school-to-college-and-career’ pipeline; and Personalization and the elusive quest for equity Personalized learning is one of the most important developments in educational reform and renewal toward a more socially just, egalitarian system with the potential to engage students fully in their learning and in their communities. However, there are many pitfalls along the road to implementation, from the problem of stagnant mindsets and mental models to corporate hijacking of the discourses around personalization. This essay highlights ways that we might best avoid these snares, so that the full power of personalized learning might be realized.
Keywords: personalized learning; John Dewey; middle school; social justice